Criminal responsibility for intentionally transmitting the corona virus (covid19) - Benmessaoud, Chahrazed (Journal of Human Sciences, 2022)
There is no doubt that human life and the right to bodily integrity are among the rights guaranted by the constitution and the law, therefore the legislator hastened to impose the severe penalities in case of violation, whether by resorting to the traditional means or the newly developed methods including the corona virus, the crime of transmitting infection with the corona virus is one of the new topics in this ira because of the medical and legal problems that is raises and its importance increases in view of the seriousness of the dusty effects of its spread and the speed of its transmission there for various countries rushed to find a legal system contribute to limiting its spread so it was necessary to activate the criminal law by approving the criminal responsibility and when its established the legal descriptions of his criminal act multiply according to the achievement of the criminal result.